Valorization of Waste Cooking Oil into Liquid Organic Fertilizer by Anaerobic Fermentation Method - Budi Santoso; Arista Putri Permatasari; Sisilia Pratama; Prahady Susmanto; R.R. Yunita Bayu Ningsih (Politeknik Negeri Malang, 2023)
Liquid organic fertilizer is a type of fertilizer that has a liquid form with a brownish color and is commonly used in agriculture as a supporting material for the main fertilizer. Liquid organic fertilizer can be produced through the fermentation process of organic matter, such as plant residues, animal or human waste, and organic waste so that it will not damage the environment. The manufacture of liquid organic fertilizer in this study uses waste cooking oil as raw material which will be fermented anaerobically for 21 days with the use of EM4 activator volume of 10 mL and 50 mL. This study was conducted to determine how much potential used cooking oil waste can be converted into liquid organic fertilizer. The results showed that the best concentration of nitrogen, phosphorus, potassium, and carbon organic in liquid organic fertilizer was obtained at 10 mL volume of EM4 activator. The best nitrogen concentration is 0.520 ppm, the best phosphorus concentration is 12.213 ppm, the best potassium concentration is 12013.825 ppm, and the best organic carbon concentration is 2.10%.